A Quality Improvement Approach to External Infliximab Infusions in Pediatric Inflammatory Bowel Disease. Issue 5 (November 2019) - Gupta, Shivani R.; Crandall, Wallace V.; Donegan, Amy; Johnson, Marci; Drobnic, Barbara; Oates, Melanie; Boyle, Brendan; Maltz, Ross M.; Dotson, Jennifer L.
ABSTRACT: Objectives: We used a quality improvement (QI) approach to improve access and reduce barriers to care by increasing the number of external infliximab infusions at our pediatric inflammatory bowel disease center. Methods: Using an iterative QI strategy, pediatric patients ≥12 years of age with inflammatory bowel disease were offered the opportunity to receive infliximab infusions at home/an external infusion center. They were required to first have >5 infusions at the hospital without any significant infusion reactions. Data were collected and tracked monthly using P-charts. Comparisons between control chart centerlines were analyzed using the Fisher exact test. Results: Fifty-four patients received external infusions, 87% had Crohn disease, 63% boys, average age 17.6 ± 2.9 years, and 89% with private insurance. From September 2016 to January 2018, the percentage of eligible patients receiving external infusions was approximately 7%, increasing to approximately 30% by January 2018. A centerline shift, representing a statistically significant change, occurred in October 2016 and June 2017 ( P < 0.001). No serious safety concerns have occurred. Conclusions: Through a multidisciplinary team of stakeholders using QI strategies, we now offer external infusion service options to all appropriate patients as routine practice. Home infusions are a viable option to reduce barriers to care, and our patients did not experience any safety events. Abstract : Supplemental Digital Content is available in the text